An overload hypothesis for pulmonary clearance of UICC amosite fibres inhaled by rats. Issue 3 (August 1983) - Bolton, R E; Vincent, J H; Jones, A D; Addison, J; Beckett, S T
Abstract : Two types of experiments were carried out to examine the effects of deposition and clearance on the accumulation in the lungs of rats of inhaled fibres of UICC amosite. In the first experiment the mass lung burdens of the dust in question were measured as a function of the time at which animals were killed after the cessation of the six week exposure period, and in the second the masses were measured for rats removed from exposure and killed at intervals during the exposure period itself. The experimental conditions were chosen to complement those of earlier work. Taken together with the results of that earlier work, the new results provide the basis for a simple mathematical model of the kinetics of deposition and clearance which appears to account for the major observed trends. Most significantly, there is strong evidence for an overload of clearance at high lung burdens (exceeding about 1500 micrograms/rat), in which a breakdown occurs of the intermediate rate clearance mechanisms (time constants of the order of 12 days). This hypothesis is supported for inhaled asbestos dust, quartz dust, and diesel fume by results obtained elsewhere. Biological explanations for the clearance overload hypothesis are at present speculative, involving discussion of the role of the macrophage in pulmonary clearance. It is believed that the clearance overload hypothesis could have possible consequences for people occupationally exposed to airborne dusts.